Exploratory laparotomy for abdominal injuries in children: a retrospective review of 36 cases - Ghritlaharey, Rajendra K. (International Journal of Contemporary Pediatrics, 2025)
Background: Abdominal injuries are a major cause of morbidity and mortality in children. The objectives of the current study were to review the demographics of children with abdominal injuries (blunt and penetrating) who required laparotomy. The study also aimed to identify the causes of injuries, organs involved, and outcomes of the surgical therapy provided. Methods: This retrospective and descriptive study was conducted for a period of 10 years from January 1, 2013, to December 31, 2022, at the author’s department of Pediatric Surgery. The study included children aged ≤12 years who needed exploratory laparotomies for abdominal injuries caused by either blunt or penetrating trauma. Results: During the study period, 36 children (30 boys and 6 girls) needed laparotomy for the management of abdominal injuries. Most children were aged 7 to 12 years (n=30; 83.33%). Indications for abdominal exploration included bowel perforation (n=20), penetrating abdominal injuries (n=9), and hemoperitoneum (n=7). Fifteen children were treated with repair or resection of bowel perforation(s). Nine required the creation of an ileostomy. Four children underwent splenectomy for shattered splenic injuries. Two deaths were documented. Conclusions: Children aged 7 to 12 years were the most frequently injured, and this study also evidenced male preponderance. Bowel perforation(s) were documented in two-thirds of children. One-fourth of the cases needed the creation of a temporary terminal ileostomy for managing their bowel injuries.